Spirituality and Pedagogy - Poškus, Kazys (Acta Paedagogica Vilnensia, 1993)
Education has been despiritualized during the Soviet years, so following the restoration of the independent Lithuania, first of all spirituality is actualised, which should essentially change the concept of pedagogy and its methodology. Unfolding the phenomenon of spirituality it should be noted that the greatest influence on it comes from morality and moral upbringing. The concepts of “creativity”, “creation” is also important for spirituality. Nationality is no less important in the present situation. It is precisely these qualities that a pupil and a teacher must have. Professional directedness is also very significant for educator spirituality: noble purpose in life, the need for high culture, humanist interests, correct orientation with regard to morality and values, robust worldview. Organizational and communication skills are also not alien to educator’s spirituality. On the other hand, during the Soviet years spirituality was neglected and pedagogy often was a theory of totalitarian partocratic education. Hence the pressure to answer a number of questions today: Are teachers themselves are spiritual enough to be able to educate their students’ spirituality?; Is it possible to develop spirituality without the help of religion?; What should be the content of education?